The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/lary.26177
|View full text |Cite
|
Sign up to set email alerts
|

Midcervical scar satisfaction in thyroidectomy patients

Abstract: 4 Laryngoscope, 127:1247-1252, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 20 publications
5
41
0
2
Order By: Relevance
“…Until now, we have not had a reliable way to measure how observers allocate attention to neck scars, which left us unable to make meaningful assessments about how to improve surgery outcomes. This research also correlates with both Western and Eastern data supporting the assertion that an incision in the central neck causes some patients to feel self‐conscious and seek subsequent intervention to minimize the impact of this incision …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Until now, we have not had a reliable way to measure how observers allocate attention to neck scars, which left us unable to make meaningful assessments about how to improve surgery outcomes. This research also correlates with both Western and Eastern data supporting the assertion that an incision in the central neck causes some patients to feel self‐conscious and seek subsequent intervention to minimize the impact of this incision …”
Section: Discussionsupporting
confidence: 74%
“…This research also correlates with both Western and Eastern data supporting the assertion that an incision in the central neck causes some patients to feel self-conscious and seek subsequent intervention to minimize the impact of this incision. 36 It is beyond the scope of this article to ascertain individual patient and observer factors that affect scar perceptions, but using eye tracking to objectively measure social attention of deformities such as neck scars can be helpful to more accurately define the characteristics of the deformity that render it worthy of attention and the point at which it does attract attention. This can help us direct our efforts; for example, observers gazed more on the neck in patients with thyroid neck scars, suggesting that avoidance of a central neck incision may be important in reducing this distraction.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been the standard approach for more than 100 years, it does leave a permanent cervical scar that may heal in a variable fashion. Some patients find this troubling and seek other options to minimize the scar …”
Section: Introductionmentioning
confidence: 99%
“…Some patients find this troubling and seek other options to minimize the scar. [2][3][4][5] Richmon et al in a cadaver, 6,7 demonstrated the feasibility of a transoral vestibular technique. It was brought to clinical practice in 2014 8 with the endoscopic approach and was reported to be safe and effective in a larger series of patients in 2016.…”
Section: Introductionmentioning
confidence: 99%
“…2 Despite these improvements, studies have demonstrated that there can be a significant negative impact on patient quality of life (QOL) as a result of a visible cervical scar. 3 Moreover, it is not only the severity or length of the scar but the mere presence of one that leads to this finding. 4 International communities, most notably in Asia, have made significant strides in remote access and minimally invasive thyroidectomy while demonstrating safety profiles similar to those through a traditional anterior cervical incision.…”
Section: Introductionmentioning
confidence: 99%